Spirulina Flour-based Feed Additive Improves the Physical and Chemical Eggs Quality of Tegal-Laying Duck - Sunarno, Sunarno; Nur Handyka, Muhammad Ammar; Mulyani, Sri; Suparmi, Suparmi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Spirulina is a species of blue green algae that contains many phenolic compounds, phytonutrients and pigments which have potential as a feed additives to improve the physical and chemical quality of eggs. The present study evaluated the effect of spirulina flour-based feed additive supplementation during the late growth to the early egg-laying period on Tegal-laying ducks' physical and chemical egg quality. A total of 25 ducks were randomly divided into 5 treatments; the control group treated with standard feed (P0), P1, P2, P3, and P4 were treated with standard feed supplemented by spirulina flour-based feed additive at concentrations of 0.3%, 0.6%,1.2%, and 2.4%, respectively for four weeks. Physical quality indicators included the Haugh unit, yolk index, weight measurements, eggshell thickness, and shape index. Chemical quality indicators assessed albumen protein content, egg yolk cholesterol, and b-carotene levels. This research revealed that spirulina flour, added at concentrations between 0.30% and 2.40%, significantly enhanced the egg quality of Tegal-laying ducks compared to the control group. This study concludes that spirulina flour can be used as a feed additive to improve the physical and chemical quality of Tegal-laying ducks’ egg. The novelty of this research is spirulina flour has the potential to be used as a feed additive to increases the albumen protein levels, increases b-carotene, and reduces egg yolk cholesterol in eggs of Tegal-laying ducks. Spirulina flour can be a potential source of feed additive for various other local ducks in Indonesia.